New species of Procinnus Herbin and Micrallo St Laurent and C. Mielke (Lepidoptera, Mimallonidae, Druenticinae) from the Brazilian Cerrado - Laurent, Ryan A. St; Mielke, Carlos G. C. (Zootaxa, 2019)
Two new species of Mimallonidae are described from the Brazilian Cerrado. One species belongs to Procinnus Herbin, 2016 and the second to Micrallo St Laurent and C. Mielke, 2016, both considered to belong to Druenticinae St Laurent and Kawahara, 2018. Procinnus incanus sp. n. is described from Bahia, Goiás, Distrito Federal, Minas Gerais, and São Paulo and is characterized by its wing habitus and male genitalia. Micrallo macro sp. n., the second species to be placed in Micrallo, is described from Minas Gerais. It differs from M. minutus St Laurent and C. Mielke, 2016 by larger size and distinct genitalia of both the male and female. All taxa involved are figured along with their genitalia. Holotypes designated here are deposited in the Coll. Padre Jesus S. Moure, in the Departamento de Zoologia, Universidade Federal do Paraná, Curitiba, Paraná, Brazil.